Route map Louise A. Boyd Arctic expeditions 1926-1955 / prepared for Miss Louise A. Boyd by William Briesemeister at the American Geographical Society of New York, 1954, revised 1956 - Boyd, Louise Arner, 1887-1972 (American Geographical Society of New York, 1956)
Black line print.; Shows the following expedition routes: 1926 M/S Hobby, 1928 M/S Hobby, 1931 S.S. Veslekari, 1933 S.S. Veslekari, 1937 S.S. Veslekari, 1938 S.S. Veslekari, 1941 M/S Morrissey, 1955 DC4 N.P. Flight. Color 1:8,000,000 not 1:4,000,000.